Indigenous Erasure and Resistance in the Caribbean - Elizabeth Wong (Caribbean Studies Students' Union, 2023)
Indigeneity has, for the most part, been absent in literature on the Caribbean, even in de-colonial writing. Writing on the Caribbean has often portrayed Indigenous people as extinct and thus as irrelevant to contemporary life in the Caribbean. Yet Indigenous peoples have played and continue to play a central role in Caribbean politics. This essay discusses how and why Indigenous people have been erased from discourse on the contemporary Caribbean. I argue that Indigenous erasure is a longstanding colonial tactic that is still used to justify the dispossession of Indigenous peoples. Drawing on the case of the Maya peoples' struggle for land in Belize, I describe some of the ways that Indigenous people continue to resist colonial and capitalist violence. Having identified and historicized the myth of Indigenous erasure in the Caribbean, I begin to sketch possibilities for shifting the discourse on the Caribbean such that it highlights rather than ignores the historical and ongoing contributions of Indigenous communities to the Caribbean. I suggest that diaspora and entanglement are two concepts that may be helpful for clarifying the Caribbean's complex colonial histories in a way that underscores the importance of Indigenous peoples to the Caribbean.